Penambahan Tepung Rumput Laut Euchema cottoni Hasil Fermentasi EM-4 Dengan Molase dan Tanpa Molase Pada Pakan Ikan Nila (Oreochromis niloticus) - Imron, Imron (Journal of Fish Nutrition, 2023)
The purpose of this study was to analyze the effect of adding fermented seaweed powder using molasses and without molasses in the feed. This research was conducted at the Laboratory of Fish Production and Reproduction, University of Mataram for 50 days from September to October 2022. This research used an experimental method with a completely randomized design (CRD) consisting of 3 treatments and 5 replications. The treatments tested were control (P1), E. cottoni seaweed flour fermented without molasses (P2), E. cottoni seaweed flour fermented using molasses (P3). Data were analyzed using analysis of variance (ANOVA) at the 5% level with a 95% confidence interval and continued with Duncan's test. The results of the 50-day rearing period showed that the average absolute weight of tilapia ranged from 4.79-5.49 g, absolute length ranged from 4.36-5.43 cm, and specific growth rate ranged from 1.60-1. .78% per day. Meanwhile, feed utilization efficiency (EPP) values ​​ranged from 63-68%, feed conversion ratio (FCR) ranged from 1.58-1.74 and survival (SR) ranged from 96-98%. While the average temperature is 27-30oC, the average pH value is 7.4-8.5, and the average DO value is between 4.5-8 m/mL. The conclusion of this study was that the addition of fermented E. cottoni seaweed flour had a significant effect on absolute weight, absolute length, specific growth rate, feed conversion ratio, feed utilization efficiency, and the fermentation process using molasses could be an alternative for growing tilapia.